Workforce shift scheduling at aircraft line maintenance with cumulative demand modelling - Altay, Gökhan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This study aims to do overall shift assignments of aircraft line maintenance crew to satisfy line maintenance tasks in time. These tasks can only be satisﬁed by maintenance crew with necessary qualiﬁcations. Therefore, shift assignments are done for tasks that require a speciﬁc qualiﬁcation. Main objective of this study is to prevent the delay due to not having workforce ready to satisfy maintenance tasks. At our model, we generated desired manpower demand schedule to monitor maintenance crew shift assignments to satisfy maintenance tasks earlier or to keep more worker ready for unplanned demand cases. Moreover, we also consider planned demand schedule coming from maintenance tasks of airplanes that is required to be satisﬁed in time. We formulated both demand schedules as cumulative in order to assign maintenance workers near desired demand schedule while being able to satisfy planned demand in time. We used Cplex to solve this model. We noticed that Cplex doesn’t perform good for all problem instances. Therefore, to support performance of the Cplex solver, we also oﬀered a simulated annealing algorithm to improve results. This problem is tested for diﬀerent amounts of airplanes, workforce, planning horizons and demand patterns and results are evaluated.
Keywords: Aircraft industry.; Aircraft industry -- Maintenance and repair.